Knowledge, perceptions and practices related to cystic echinococcosis in families with history of this illness - Ramírez D., Yelina (2018)
The aim of this study was to systematize information about the knowledge, perceptions and practices associated with exposure to Echinococcus granulosus in families with a history of cystic echinococcosis (EQ) from the province of Huancayo, Junín region (Peru), attended at the National Institute of Child Health during the period 2004-2012. An interview guide was developed and applied to the family member closest to the case of the patient with EQ, but allowing the intervention of other members. Extracts from the transcription of the audios were categorized as risk factors for contracting the disease, impacts on the patient and the family, and change produced in the post disease environment. The quantitative section was summarized on descriptive statistics. It was demonstrated the persistence of deficiencies in the knowledge, perceptions and practices of the interviewees and their families regarding the EQ. Families maintain habits and practices that favour the transmission and dissemination of the disease. The experience of suffering the disease years ago has not produced positive changes in their lifestyles. It is hoped that the results serve as antecedents to act against the social aspects of this disease.